The Issues of Recognition of the Anamburung Customary Law Community in East Sumba - Warandoy, Febri umbu Nggau; Nurjaya, I Nyoman; Herlindah, Herlindah (NEGREI: Academic Journal of Law and Governance, 2023)
The system of living together creates culture, as each member of the group feels bound to one another. Indigenous communities are groups of people who interact in social relations with a common culture, territory, and identity. In East Sumba, the lack of recognition and protection through the Permendagri has led to differences in perception between indigenous peoples and the government regarding customary land and state assets. Over three decades, national development focusing on economic growth has resulted in disputes between the government, business actors, and indigenous communities. The Permendagri has not yet addressed the dispute resolution process, and no local regulation exists for the transfer of unregistered customary land, creating a legal vacuum. This study uses socio-legal research methods to examine the reality of dispute resolution of customary land rights between the government and the Anamburung Customary Law Community of East Sumba. The research concludes that disputes over customary land rights in this community involve various historical, social, and legal factors, and the lack of socialization regarding customary land status and boundaries allows powerful groups to claim land as state property without community consent.